Ovarian Vein Thrombosis Presenting as Acute Abdomen in Puerperium - Flavia Sorbi; Luca Mannini; Martina Aldinucci; Viola Ghizzoni; Massimiliano Fambrini (Journal of Clinical and Diagnostic Research, 2016)
Postpartum Ovarian Vein Thrombosis (POVT) is a rare, but serious condition that causes slow quadrant pain in the postpartum period. POVT must be considered in the differential diagnosis of postpartum acute abdomen. We hereby report a case on a 36-year-old Italian woman who developed an acute abdomen a week after spontaneous vaginal delivery. She had persistent fever and constipation. Diagnosis of POVT was made with an abdominal Computed Tomography (CT) and treatment with heparin and broad-spectrum antibiotics were started. After 72 hours, the patient was switched from low molecular weight heparin to oral anticoagulant treatment. After 5 months a complete recanalization was demonstrated by abdomen CT and the treatment was stopped 6 months after diagnosis. POVT is a diagnosis of exclusion in the puerperium. This case illustrated that POVT may also occur in low risk patient.